MODERN METHODS OF PHYSICAL THERAPY FOR SCOLIOTIC POSTURE IN ADOLESCENTS: PROSPECTS OF THE SENSORIMOTOR APPROACH (Physical Culture and Sport: Scientific Perspective, 2025)
The problem of postural disorders, including scoliotic posture, remains highly relevant during adolescence due to intensive skeletal growth, postural instability, and functional muscle imbalance. This paper presents an overview of modern physical therapy methods for correcting scoliotic posture in adolescents, with an emphasis on current neurophysiological and sensorimotor approaches. Traditional interventions such as therapeutic exercises, respiratory gymnastics, and the Schroth method have demonstrated positive effects on muscle tone and body alignment. However, they are limited in addressing proprioceptive deficits and postural control mechanisms.The article highlights the clinical rationale for integrating sensorimotor stimulation techniques–particularly exercises on unstable surfaces, proprioceptive neuromuscular facilitation (PNF), and myofascial taping. These components enhance trunk stabilization, improve proprioceptive feedback, and promote the formation of new postural motor patterns. A comparative matrix is presented to match key postural dysfunctions (such as core weakness, poor proprioception, and asymmetry) with evidence-based therapeutic strategies.The findings support the feasibility of developing a short-term, modular sensorimotor-stabilization program adapted to outpatient or school-based rehabilitation settings. This program targets three correctional levels–neurophysiological, motor-functional, and behavioral-motivational–thus providing a holistic framework for posture correction in adolescents. Future research should focus on clinical testing and standardization of such protocols for broader implementation in pediatric physical therapy.
Keywords: anatomical and biomechanical postural disorders; adolescents; physical therapy; sensorimotor training; PNF; taping; postural stability